GAMBARAN DAMPAK SIKAP TERHADAP UANG (money attitude) PADA PERILAKU PENGELOLAAN KEUANGAN PRIBADI - Marissa Silooy (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
Financial management is a set of behaviors carried out through planning, budgeting, and evaluating which includes cash, credit, investment, insurance and retirement, and inheritance planning activities. Financial management practices in the younger generation have received serious attention from various organizations, such as governments, financial institutions, universities, and others. This is because when they began to enter the world of lectures, most of them did not have a sense of responsibility towards their own personal finances also showed that today's young generation rarely practiced basic financial capabilities, such as budgeting, daily savings planning or planning for long-term needs. To answer the research problem, researchers use the Money Attitude Scale (MAS) developed by Yamauchi & Templer (1982), which is a valid measurement tool in assessing the impact of attitudes on money on personal financial management, namely: (1) power-prestige, showing the use of money as a tool to influence and impress others and as a symbol of success, (2) retention-time, describes the use of money directed to the future, which requires financial planning. People with a retention-time attitude will be careful when using money and are very concerned with the financial situation that occurs. The results showed power prestige, retention-time.Keywords: Impact of attitude towards money (money attitude), personal financial management behavior